A construção da imagem pública das parlamentares paraibanas eleitas para a Assembleia Legislativa no pleito de 2010 - Nogueira, Maria Janilma Pereira (2014)
This dissertation aims to analyze the process of building the public image of four state deputies occupying a seat in the “Assembléia Legislativa”, located in the city of João Pessoa, Paraíba. They are: Léa Toscano, Iraê Lucena, Daniella Ribeiro and Gilma Germano. Our purpose is to understand, through the reports uttered during interviews with these parliamentarians, how they placed themselves in politics, what they think about that universe and what are their future plans in that sphere. The theoretical basis of our work is related to the literature that deals with the political inclusion and participation of women, as well as on political culture and public image building. We know that for too long women have been excluded from this area of power, being men mostly the universal protagonists of the political scene. The participation in political fields as active citizens was only granted to our women after several struggles for rights. Persons that always have lived in a subordinate situation, women are currently managing to break down the barriers of prejudice and gender discrimination. It can see, in the speech of parliamentarians interviewed, strong trace of a policy anchored on the family name and this justified precisely because all had as input in public life the family heritage. It is also evident in the discourse of informants that women as candidates tend to use symbols that refer to ethics and morality, or even "feminine values" that always have been allocated to "natural" way simply because they are women, such as: sensitivity, gentleness, sincerity, kindness, among others. All this works, however, for political women in general, as an strategy affirmation in this power space.